Jawabanmu

2014-05-11T22:32:29+07:00
L i m  x - √(2x + 3) = l i m x - √(2x + 3) . x + √(2x + 3)
x⇒3    9 - x²            x⇒3       (9 - x²)  (x + √(2x + 3)
                               l i m  x² - (2x + 3)
                              x⇒3 (9 - x²)(x+√(2x+3)
                               l i m          x² - 2x - 3
                                x⇒3 (9 - x²)(x+√(2x+3)
                               l i m    (x - 3)(x + 1)     
                               x⇒3(x-3)(x+3)(x+√(2x+3)
                               l i m          x + 1                 
                               x⇒3 (x+3)(x+√(2x+3)
                              =              3 + 1                     
                                   (3+3)(3 + √(6+3)
                               =             4                
                                         6(3 + 3)
                               =4/36
                               = 1/9